Fontinalis sullivantii and F. dichelymoides (Fontinalaceae, Bryophyta)—synonyms or distinct species? - Latoszewski, Mikołaj; Buck, William R.; Wolski, Grzegorz J. (Phytotaxa, 2026)
The genus Fontinalis is recognized as one of the most taxonomically challenging groups of mosses due to its high morphological variability and divergent species concepts applied in North America and Eurasia. This study presents a detailed morpho-anatomical re-evaluation of the type material of Fontinalis sullivantii and F. dichelymoides to clarify their taxonomic boundaries. An analysis of 38 qualitative and quantitative characters revealed distinct differences between the type specimens of both taxa. Key diagnostic features include leaf dimensions, auricle morphology, and stem anatomy. Fontinalis dichelymoides is distinguished by narrower, nearly needle-like leaves, strongly inflated, subglobose to ovoid, and sharply delimited auricles, as well as significantly larger stem epidermal cells compared to F. sullivantii. The results indicate that both names represent distinct morphological entities. Consequently, the synonymization of F. dichelymoides under F. sullivantii, as proposed in some North American works, is not supported by the morphological and anatomical characteristics of their respective type materials. This work represents a necessary step towards stabilizing the nomenclature of the genus and revising the geographic ranges of both species.